Optimizing Ecotourism Elements to Strengthen the Tourism Attraction of Kerta Village, Payangan, Gianyar - Pramartha, I Made Aditya; Putra, I Komang; Aryasa, I Putu Gde Chandra Artha (Asian Journal of Community Services, 2024)
Kerta Village has ecotourism potential that has not been optimized, such as the potential of waterfall attractions, MSME products, and agro-tourism potential of orange plantations. The problems faced are the optimal management of the potential owned, the lack of supporting infrastructure, and the limited capacity of the community in managing potential. This service activity aims to optimize the ecotourism potential of Kerta Village to strengthen tourist attraction. The methods used include field surveys, master plan planning, and community assistance. The results show that with the master plan for the establishment of water attractions can strengthen the tourist attraction of Kerta Village. synergy between ecotourism development and MSME empowerment is important in order to create a mutually reinforcing economic ecosystem.